2006
DOI: 10.1007/s10551-005-5586-y
|View full text |Cite
|
Sign up to set email alerts
|

Principal Theory and Principle Theory: Ethical Governance from the Follower’s Perspective

Abstract: Organizational governance has historically focused around the perspective of principals and managers and has traditionally pursued the goal of maximizing owner wealth. This paper suggests that organizational governance can profitably be viewed from the ethical perspective of organizational followers – employees of the organization to whom important ethical duties are also owed. We present two perspectives of organizational governance: Principal Theory that suggests that organizational owners and managers can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…The evolution of governance models, presented by stakeholder theory and stewardship theory, extends the company's obligations beyond shareholders and this is based on the assumption that the company has responsibilities to society and a variety of ethical and moral obligations (Caldwell, Karri, & Vollmar, 2006).…”
Section: Stewardship and The Effects On Human Resource Management Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of governance models, presented by stakeholder theory and stewardship theory, extends the company's obligations beyond shareholders and this is based on the assumption that the company has responsibilities to society and a variety of ethical and moral obligations (Caldwell, Karri, & Vollmar, 2006).…”
Section: Stewardship and The Effects On Human Resource Management Andmentioning
confidence: 99%
“…Goffee and Jones (2001, as cited by Caldwell et al, 2006) mentioned that leaders must build relationships with employees to develop a sense of commitment in a competitive global market. This brings systems management practices of human resources, called collaborative or partnership/alliance (Lepak & Snell, 1999;López Cabrales et al, 2009;Martínez Lucio & Stuart, 2005).…”
Section: Stewardship and The Effects On Human Resource Management Andmentioning
confidence: 99%
“…Caldwell and Karri (2005, p. 254) framed the role of the steward as an ''integrator of shared interests'' with a responsibility to help the organization and its members to self-actualize. Caldwell et al (2006) noted that the duties of stewards were fraught with a complex set of ethical obligations. Caldwell et al (2008) suggested that great leaders practiced ''ethical stewardship'' by pursuing the optimization of wealth creation through creating relationships that maximized stakeholder ownership and commitment.…”
Section: Ethical Stewardship As a Theory Of Governancementioning
confidence: 99%
“…McClusky, 2002;Steinberg and Pojunis, 2000). Although stewardship theory is most commonly compared with agency theory and stakeholder theory, two new theories of governance called principle theory and principal theory also offer insights about the ''covenantal'' nature of the leader's role (Caldwell et al, 2006). Barney and Hesterley (1996) suggested that businesses commonly choose a governance form based upon problems created by bounded rationality and opportunism -even though the form of governance substantially impacts both leader behaviors and organizational culture (Thomsen, 2005).…”
Section: Ethical Stewardship and The Leadership Rolementioning
confidence: 99%
“…Carroll (1996, p. 23) explained that the task of management under stakeholder theory was to ''reconcile the conflicts of interest that occur between the organization and the stakeholder groups.'' Principal theory proposed that it was the principal rather than the agent who was prone to act with opportunism to the detriment of other stakeholders -hiring the manageror agent to carry out the task of achieving short-term profits at the expense of long-term wealth creation (Caldwell et al, 2006). Principle theory described a governance approach that pursued a set of guiding principles -sometimes to excess -resulting in suboptimization of results because ideal principles and their rigid application may be either inappropriate for every situation or misapplied by unskilled practitioners (Caldwell et al, 2006).…”
Section: Ethical Stewardship and The Leadership Rolementioning
confidence: 99%